Characterisation of the Introgression of Brassica villosa Genome Into Broccoli to Enhance Methionine-Derived Glucosinolates and Associated Health Benefits - Neequaye, Mikhaela; Steuernagel, Burkhard; Saha, Shikha; Trick, Martin; Troncoso-Rey, Perla; van den Bosch, Frans; Traka, Maria H.; Østergaard, Lars; Mithen, Richard (Frontiers in Plant Science, 2022)
Broccoli cultivars that have enhanced accumulation of methionine-derived glucosinolates have been developed through the introgression of a novel allele of the MYB28 transcription factor from the wild species Brassica villosa. Through a novel k-mer approach we characterised the extent of the introgression of unique B.villosa genome sequences into high glucosinolate broccoli genotypes. RNAseq analyses indicated that the introgression of the B.villosa MYB28 C2 allele resulted in the enhanced expression of the MYB28 transcription factor, and modified expression of genes associated with sulphate absorption and reduction, and methionine and glucosinolate biosynthesis compared to standard broccoli. An AT short tandem repeat was identified within the 5’ UTR B.villosa MYB28 allele that was absent from two divergent cultivated forms of B.oleracea which may underpin the enhanced expression of B.villosa MYB28.